Carbohydrate‐based vaccines for oncotherapy. Issue 3 (7th March 2018) - Wei, Meng‐Man; Wang, Yong‐Shi; Ye, Xin‐Shan
Abstract: Cancer is still one of the most serious threats to human worldwide. Aberrant patterns of glycosylation on the surface of cancer cells, which are correlated with various cancer development stages, can differentiate the abnormal tissues from the healthy ones. Therefore, tumor‐associated carbohydrate antigens (TACAs) represent the desired targets for cancer immunotherapy. However, these carbohydrate antigens may not able to evoke powerful immune response to combat with cancer for their poor immunogenicity and immunotolerance. Different approaches have been developed to address these problems. In this review, we want to summarize the latest advances in TACAs based anticancer vaccines.